Improving antibiotic prophylaxis in gastrointestinal surgery patients: A quality improvement project. (August 2017) - Kilan, Rabie; Moran, Dane; Eid, Iyad; Okeahialam, Christopher; Quinn, Corrine; Binsaddiq, Wadie; Williams, Tammy; Johnson, Michael H.
Abstract: Background: A surgical site infection (SSI) is a frequent complication following gastrointestinal surgery, but the careful selection and administration of prophylactic antibiotics can reduce the risk. The aim of this study was to develop a package of interventions that could be used to improve surgical antibiotic prophylaxis (SAP) at our institution. Methods: A pre-post quality improvement project at a private hospital in Saudi Arabia was conducted between January 2014 until July 2016. A multidisciplinary team was assembled to identify and overcome barriers that were responsible for patients receiving suboptimal antibiotic prophylaxis. Patients were included if they had undergone surgery on their appendix, colon, rectum, or small intestine. Compliance with use of an adapted order form, as well as appropriate antibiotic selection, dosing, timing, and timing of re-dosing, were measured. Data on the rates of SSI before and after the intervention were also obtained. Results: Of the 269 patients included in the study, 161 (61.5%) had appendix surgery, 86 (32.8%) had colorectal surgery, and 15 (5.7%) had small bowel surgery. The surgery was performed laparoscopically in 218 (83.5%) of patients. Utilization of the adapted order form increased from 1.8% to 92.0% following the intervention (p < 0.001). Compliance with a bundle of appropriate antibiotic selection, dosing and timing improved from 47.3% to 82.2% after the intervention (p < 0.001). Additionally, there was a non-statistically significant reduction in SSI rate (9.1% vs 5.1%; p = 0.27). Conclusions: Our quality improvement intervention was successful in improving SAP for patients undergoing gastrointestinal surgery at our institution. Highlights: A high rate of surgical site infections was identified at our institution. A quality improvement intervention successfully increased the use of antibiotic prophylaxis. A multidisciplinary team was a key enabling factor.